Tracking nitrate and sulfate sources in groundwater of an urbanized valley using a multi-tracer approach combined with a Bayesian isotope mixing model. (1st September 2020) - Torres-Martínez, Juan Antonio; Mora, Abrahan; Knappett, Peter S.K.; Ornelas-Soto, Nancy; Mahlknecht, Jürgen
Abstract: Over the past decades, groundwater quality has deteriorated worldwide by nitrate pollution due to the intensive use of fertilizers in agriculture, release of untreated urban sewage and industrial wastewater, and atmospheric deposition. Likewise, groundwater is increasingly polluted by sulfate due to the release of domestic, municipal and industrial wastewaters, as well as through geothermal processes, seawater intrusion, atmospheric deposition, mineral dissolution, and acid rain. The urbanized and industrialized Monterrey valley has a long record of elevated nitrate and sulfate concentrations in groundwater with multiple potential pollution sources. This study aimed to track different sources and transformation processes of nitrate and sulfate pollution in Monterrey using a suite of chemical and isotopic tracers (δ 2 H–H2 O, δ 18 O–H2 O, δ 15 N–NO3, δ 18 O–NO3 δ 34 S–SO4, δ 18 O–SO4 ) combined with a probability isotope mixing model. Soil nitrogen and sewage were found to be the most important nitrate sources, while atmospheric deposition, marine evaporites and sewage were the most prominent sulfate sources. However, the concentrations of nitrate and sulfate were controlled by denitrification and sulfate reduction processes in the transition and discharge zones. The approach followed in this study is useful for establishing effective pollution management strategies in contaminated aquifers. Graphical abstract: Image 1 Highlights: Groundwater nitrate and sulfate sources and transformation were investigated. Water chemistry, stable isotopes, and a Bayesian mixing model were combined. Soil nitrogen and sewage were the most important nitrate sources. Atmospheric deposition, marine evaporites and sewage were the main sulfate sources. Contamination was controlled by denitrification and sulfate reduction processes.